2006
DOI: 10.1152/japplphysiol.00090.2006
|View full text |Cite
|
Sign up to set email alerts
|

An important functional role of persistent Na+current in carotid body hypoxia transduction

Abstract: Systemic hypoxia in mammals is sensed and transduced by the carotid body into increased action potential (AP) frequency on the sinus nerve, resulting in increased ventilation. The mechanism of hypoxia transduction is not resolved, but previous work suggested that fast Na(+) channels play an important role in determining the rate and timing of APs (Donnelly, DF, Panisello JM, and Boggs D. J Physiol. 511: 301-311, 1998). We speculated that Na(+) channel activity between APs, termed persistent Na(+) current (I(Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Thus, it is worth noting that a role for nonchemical, electrical synapses has been forwarded (248) and also that the entire premise of classical neurotransmission in the carotid body has been questioned (218, 811). Donnelly (218) observed that afferent action potentials appear not to be dependent upon synaptic depolarizing potentials in the nerve terminals, as would be expected, but instead, are linked to a process endogenous to the nerve terminals themselves whereby an increased variability in excitability is brought about by channel noise, developed by a persistent Na + current (263). In this proposal, chemicals released from type I cells during stimulation would act to modulate rather than generate the nerve terminal excitability and afferent action potentials should therefore persist in the absence of type I cells.…”
Section: Neurotransmission In the Carotid Bodymentioning
confidence: 96%
“…Thus, it is worth noting that a role for nonchemical, electrical synapses has been forwarded (248) and also that the entire premise of classical neurotransmission in the carotid body has been questioned (218, 811). Donnelly (218) observed that afferent action potentials appear not to be dependent upon synaptic depolarizing potentials in the nerve terminals, as would be expected, but instead, are linked to a process endogenous to the nerve terminals themselves whereby an increased variability in excitability is brought about by channel noise, developed by a persistent Na + current (263). In this proposal, chemicals released from type I cells during stimulation would act to modulate rather than generate the nerve terminal excitability and afferent action potentials should therefore persist in the absence of type I cells.…”
Section: Neurotransmission In the Carotid Bodymentioning
confidence: 96%
“…A recent study showed that the phenotypic signs of ASD induced by VAP exposure in rats can be significantly improved or recovered by the administration of vitamin D in early stages of development (Du, Zhao, Duan, & Li, 2017). In addition, it has been demonstrated that persistent Na + current is responsible for hypoxia in neurons leading to neuronal damages (Faustino & Donnelly, 2006). In fact, the persistence of Na + currents leads to the increased activity of Na + /Ca 2+ exchangers in neurons, itself resulting in an increase in Ca 2+ cytoplasmic concentration (Faustino & Donnelly, 2006).…”
Section: Reviewmentioning
confidence: 99%
“…In addition, it has been demonstrated that persistent Na + current is responsible for hypoxia in neurons leading to neuronal damages (Faustino & Donnelly, 2006). In fact, the persistence of Na + currents leads to the increased activity of Na + /Ca 2+ exchangers in neurons, itself resulting in an increase in Ca 2+ cytoplasmic concentration (Faustino & Donnelly, 2006). In order to correct this situation, it has been proposed that an increase in Na + influx into cells prevents trauma in the nervous system (Ates et al., 2007).…”
Section: Reviewmentioning
confidence: 99%
“…Donnelly recently showed that a persistent Na + current (I NaP ), which is sensitive to riluzole and tetrodotoxin and present only on afferent nerves, plays a critical role in carotid body O 2 -sensitivity (Faustino and Donnelly, 2006). Chemosensitivity in the afferent nerve endings is an attractive hypothesis that might explain experimental results such as the recovery of chemosensitivity in the carotid sinus nerve after removal of the carotid body (Mitchell et al, 1972), and the large variation in effects of a given neurotransmitter or neuromodulators on chemoreception between species (see below).…”
Section: Ion Channelsmentioning
confidence: 99%